ANALISIS PENGARUH MEREK, HARGA DAN KUALITAS PRODUK LARISSA AESTHETIC CENTER YOGYAKARTA TERHADAP KEPUTUSAN PEMBELIAN - Paramita Paramita; Dila Damayanti (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The purpose of this research is to know: (1) influence of brand influence to purchase decision of Larissa product (2) influence of price to decision of purchase of Larissa product (3) influence of product quality to decision of purchase of Larissa product (4) influence of brand, price, and product quality simultaneous decision to purchase Larissa products. This type of research is survey research. Population in this research is consumer of Larissa Aesthetic Center Galleria Mall. Sampling method with non probability sampling with convenience sampling with the number of 100 respondents. Data were collected with questionnaires that have been tested for validity and reliability. Data analysis technique used is multiple linear regression analysis. The result of this research show that (1) there is influence between brand to decision of purchasing of Larissa product, this is proved by result of t test statistic for Brand variable (X ) obtained t value bigger than t table (3,104> 1,985) with significance 0,003 < 0.05. So partially the brand variable (X1) has a significant effect on purchasing decisions (Y). (2) The result of t test statistic for Price variable (X‚ ) obtained t value count bigger than t table (2,905> 1,985) with significant t equal to 0,005, because t value count bigger than t table and significant t <0,05 0.005 <0.05). So partially variable brand (X‚ ) have a significant effect onpurchase decision (Y). (3) The result of t test statistic for product quality variable (Xƒ ) is got t value bigger than t table (2,445> 1,985) with significant t equal to 0,016, because t value count bigger than t table and significant t <0,05 (0.016 <0.05). So partially variable brand (Xƒ ) have a significant effect on purchasedecision (Y).